Integrating spirituality and rationality the long and arduous journey of the historical development of theological training in the Apostolic Faith Mission of South Africa - Marius Nel; Fika Janse van Rensburg (In die Skriflig, 2016)
The chequered path of the development of theological training in the Apostolic Faith Mission of South Africa (AFM of SA) started with animosity towards any form of training in favour of the presumed equipment provided by the anointment with the Spirit. Later it led to recognition of the need for better training in the form of Bible school equipment for ministering in assemblies. Finally, the need for proper theological training was acknowledged. The composition of the church’s membership and the way it was treated by other denominations influenced the way the Pentecostal Movement defined its stance towards theological training. In this article the AFM of SA’s journey and development of its viewpoint towards theological training will be discussed.